Upaya Meningkatkan Minat Belajar Siswa melalui Pemanfaatan Media Blooket Berbasis Web pada Mata Pelajaran Ekonomi Kelas X SMA Negeri 12 Pekanbaru - Ani Rustirani; Lara Mustika; Maghfira Nurzoumi Anli; Melati; Pransisko Pandiangan; Zita Barlian; Mahdar Ernita; Hastriani Tuti (STKIP Subang, 2025)
This classroom action research aims to increase students' interest in learning Economics by utilizing web-based educational media, specifically Blooket. The research employs the Kurt Lewin model, which consists of four stages: planning, action, observation, and reflection. The subject of this study was Class X-8 students at SMA Negeri 12 Pekanbaru. Data were collected through observations, student interest questionnaires, interviews, and supporting documentation, and were analyzed both qualitatively and quantitatively. The results show a significant improvement in students' learning interest between the first and second cycles. In the first cycle, the average student interest score was 70.80% (categorized as good), and it increased to 77.07% in the second cycle. The highest increases were recorded in the indicators of enjoyment (82.15%) and enthusiasm (79.44%). These findings suggest that the integration of Blooket in the learning process not only fosters a fun and competitive learning atmosphere but also encourages student motivation and active engagement, especially in learning Economics. Therefore, Blooket proves to be an effective and innovative tool in enhancing students' learning interest.